Tinjauan Kejelasan dan Ketepatan Diagnosa Pada Resume Medis Pasien Rawat Inap dengan Keakuratan Kode Berdasarkan ICD-10 di RSHD Kota Bengkulu - Salehudin, Muhammad; Harmanto, Deno; Bidiarti, Anggoa (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2021)
Problem : Completeness, clarity in filling out the medical resume form is an absolute must because all patient health data information is on the medical resume sheet, but based on an initial survey that researchers conducted on January 23, 2021 at the Harapan and Prayer Hospital in Bengkulu City , from 14 inpatient medical record documents there are 7 (50%) medical record documents that are not clearly written with the rules of ICD-10 medical terminology and 7 (50%) medical record documents are not written correctly with the ICD10 medical terminology rulesObjective: This study aims to determine the description of the clarity and accuracy of the diagnosis on the Medical Resume Sheet of Inpatients with Code Accuracy based on ICD-10 at the Bengkulu City Hospital.Methods : This type of research is a descriptive study using a cross sectional design. The population in this study was the medical record files of inpatients in April 2021, which amounted to 120 files with a total sample of sampling, using secondary data that was processed univariately. This research was carried out from 03 to 10 May 2021 at the Bengkulu City Hospital Medical Record Unit.Results : From 120 medical resume sheets for inpatients at the Harapan Hospital and Prayers in Bengkulu City, the lack of clarity in writing the diagnoses of inpatients in a small percentage of 40 diagnoses (33.3%) was not clearly written and the inaccuracy of writing diagnoses for inpatients was a small percentage of 40. diagnoses (33.3%) were written incorrectly and the determination of the diagnosis code was also a small part, namely 40 codes (33.3) were not accurate. It is expected that doctors and coders always rely on medical terminology in accordance with ICD-10 in writing patient diagnoses so that a clear, precise and accurate diagnosis is obtained